2020
DOI: 10.1101/2020.12.02.408518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Normalizing the brain connectome for communication through synchronization

Abstract: Networks in neuroscience determine how brain function unfolds. Perturbations of the network lead to psychiatric disorders and brain disease. Brain networks are characterized by their connectomes, which comprise the totality of all connections, and are commonly described by graph theory. This approach is deeply rooted in a particle view of information processing, based on the quantification of informational bits such as firing rates. Oscillations and brain rhythms demand, however, a wave perspective of informat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 119 publications
(188 reference statements)
0
7
0
Order By: Relevance
“…We propose that, beyond the connection topology imposed by the spatial scaffolding (9), the conjugate property of connectivity is temporal in nature and complementary to the structural topology (38). Together, spatial and temporal constraints reveal the topochronic framework from which oscillatory brain activity emerges.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that, beyond the connection topology imposed by the spatial scaffolding (9), the conjugate property of connectivity is temporal in nature and complementary to the structural topology (38). Together, spatial and temporal constraints reveal the topochronic framework from which oscillatory brain activity emerges.…”
Section: Discussionmentioning
confidence: 99%
“…It’s an open question that needs more investigation, and computational modeling can be helpful to solve it. Positive and negative links conceptually look the same as in-phase and anti-phase synchronizes (Petkoski & Jirsa, 2019; Petkoski & Jirsa, 2020; Petkoski et al, 2016) whereas Petkoski and his colleagues showed that in-phase synchrony (or perfectly aligned in/anti-phase clustering) makes the lowest energy which is similar to a brain signed network that has no negative links and frustrations located in the lowest balance energy. They also found that when giving the distribution of the time-delays in the brain, it is more probable that the brain minimizes the disorders that are in a way with our previous results (Saberi et al, 2021a), and the self-organizing essence of the brain (Dresp-Langley, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Fo synchronization at frequency Ω, equation 1 reads [36], The phase difference between each pair of Kuramoto oscillators is given as, For symmetric coupling C mn = C nm = c (say), Ï„ mn = Ï„ nm = Ï„ (say). In our experiment Δ ω = 0.…”
Section: Methodsmentioning
confidence: 99%